MOBILE-ASSISTED LANGUAGE LEARNING (MALL) FOR ENGLISH LEARNERS: AN INVESTIGATION OF ITS IMPACT ON VOCABULARY ACQUISITION - Shaumiwaty Shaumiwaty; James Smith; Lucy Taylor (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
Mobile technologies have become increasingly integrated into educational contexts, offering new opportunities for language learning beyond traditional classroom boundaries. In English language education, vocabulary acquisition remains a fundamental yet persistent challenge, particularly when learning opportunities are limited to formal instructional settings. Mobile-Assisted Language Learning (MALL) has emerged as a promising approach that enables flexible, repeated, and learner-centered vocabulary practice through mobile devices. This study aims to investigate the impact of MALL on vocabulary acquisition among English learners. A quasi-experimental research design was employed, involving an experimental group using mobile-based vocabulary learning applications and a control group receiving conventional vocabulary instruction. Data were collected through standardized pretest and posttest vocabulary assessments and supported by learning activity records. Statistical analyses were conducted to examine differences in vocabulary gains between groups. The results indicate that learners who engaged in MALL achieved significantly higher vocabulary gains than those in the control group. The findings also reveal that consistent engagement with mobile learning activities contributed to more stable and sustained vocabulary development. The study concludes that MALL is an effective instructional approach for enhancing vocabulary acquisition in English language learning contexts. Integrating mobile-assisted vocabulary learning into instructional practices can support improved learning outcomes and provide learners with greater autonomy and access to language input.